Climate change and extreme weather disasters: evacuation stress is associated with youths’ somatic complaints - La Greca, Annette M.; Burdette, Evan T.; Brodar, Kaitlyn E. (Frontiers in Psychology, 2023)
Objective Climate-change has brought about more frequent extreme-weather events (e.g., hurricanes, floods, and wildfires) that may require families to evacuate, without knowing precisely where and when the potential disaster will strike. Recent research indicates that evacuation is stressful for families and is associated with psychological distress. Yet, little is known about the potential impact of evacuation stressors on child health. After Hurricane Irma, which led to a mass evacuation in Florida, we examined whether evacuation stressors and hurricane exposure were uniquely associated with youth somatic complaints, and whether youth psychological distress (i.e., symptoms of posttraumatic stress, anxiety, and depression) served as a potential mediating pathway between evacuation stressors, hurricane experiences, and somatic complaints. Method Three months after Irma, 226 mothers of youth aged 7–17 years (N=226; M age = 9.76 years; 52% boys; 31% Hispanic) living in the five southernmost Florida counties reported on evacuation stressors, hurricane-related life threat and loss/disruption, and their child’s psychological distress and somatic complaints using standardized measures. Results Structural equation modeling revealed a good model fit (χ2 = 32.24, p = 0.003, CFI = 0.96, RMSEA = 0.08, SRMR = 0.04). Even controlling for life-threatening hurricane experiences (β = 0.26) and hurricane loss and disruption (β = 0.26), greater evacuation stressors were associated with greater symptoms of youth psychological distress (β = 0.34; p’s < 0.001), and greater psychological distress was associated with more somatic complaints (β = 0.67; p < 0.001). Indirect effects revealed that evacuation stressors (p < 0.001), actual life-threatening events (p < 0.01), and loss and disruption (p < 0.01) were all uniquely and indirectly associated with youths’ somatic complaints via youth psychological distress. Discussion Findings suggest that even coping with the threat of a disaster may be sufficient to prompt psychological and physical health symptoms in youth. Due in part to climate change, threats of disaster occur much more often than actual disaster exposure, especially for areas that are prone to hurricanes or wildfires. Preparing youth and families residing in vulnerable areas for potential disaster evacuation or sheltering-in-place appears critical. Encouraging families to develop Disaster Plans and teaching stress management skills may reduce both youth distress and somatic health problems.